The Buy-to-Build Indicator: New Estimates and Comment - Joseph Francis; Shimshon Bichler; Jonathan Nitzan (The Bichler and Nitzan Archives, 2013)
The first part of the exchange is a short article by Joe Francis. The article provides new long-term estimates and an assessment of the buy-to-build indicator for the United States and Britain, going back to the beginning of the 20th century. The second part offers commentary by Shimshon Bichler and Jonathan Nitzan.
Keywords: 330; Britain; M&A; measurement; methodology; stagflation; United States